Evaluation of skin cancer chemoprevention potential of sunscreen agents using the Epstein–Barr virus early antigen activation in vitro assay. (28th November 2012) - Kapadia, G. J.; S. Rao, G.; Takayasu, J.; Takasaki, M.; Iida, A.; Suzuki, N.; Konoshima, T.; Tokuda, H.
Synopsis In our continuing search for novel cancer chemopreventive compounds of natural and synthetic origin, we have evaluated 14 commonly used ultraviolet (UV) sunscreen agents (designated UV‐1 to UV‐14) for their skin cancer chemoprevention potential. They belong to 8 different chemical categories: aminobenzoate (UV‐5, UV‐7, UV‐8 and UV‐14), benzophenone (UV‐1, UV‐2, UV‐3 and UV‐13), benzotriazole (UV‐10), benzyloxyphenol (UV‐9), cinnamate (UV‐6), quinolone (UV‐4), salicylate (UV‐11) and xanthone (UV‐12). In the in vitro assay employed, the sunscreens were assessed by their inhibition of the Epstein–Barr virus early antigen (EBV‐EA) activation induced by the tumour promoter 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA) in human lymphoblastoid Raji cells. All sunscreens tested were found to exhibit anti‐tumour promoting activity: listed in decreasing order, moderate (UV‐11, UV‐2, UV‐7, UV‐12, UV‐3, UV‐9 and UV‐14) to weak (UV‐1, UV‐6, UV‐8, UV‐16, UV‐5, UV‐4 and UV‐10) with octyl salicylate (UV‐11) as the most potent and drometrizole (UV‐10) as the least potent among the compounds evaluated. A plausible relationship between the antioxidant property of sunscreens and their ability to promote anti‐tumour activity was noted. The results call for a comprehensive analysis of skin cancer chemoprevention potential of currently used UV sunscreen agents around the globe to identify those with the best clinical profile.